2015
DOI: 10.32607/20758251-2015-7-3-133-139
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin Inhibits Growth of Breast Cancer Cells: The Role of ERα and HER2/neu

Abstract: Phytoestrogens are a group of plant-derived compounds with an estrogen-like activity. In mammalians, phytoestrogens bind to the estrogen receptor (ER) and participate in the regulation of cell growth and gene transcription. There are several reports of the cytotoxic effects of phytoestrogens in different cancer cell lines. The aim of this study was to measure the phytoestrogen activity against breast cancer cells with different levels of ER expression and to elucidate the molecular pathways regulated by the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…For this reason, we propose that (−)-epicatechin could be acted by a different mechanism. Although the effects of (−)-epicatechin on ER-positive and ER-negative breast cancer cells are consistent with observations with other flavonoids [35][36][37], the cellular targets remain unknown.…”
Section: Discussionsupporting
confidence: 72%
“…For this reason, we propose that (−)-epicatechin could be acted by a different mechanism. Although the effects of (−)-epicatechin on ER-positive and ER-negative breast cancer cells are consistent with observations with other flavonoids [35][36][37], the cellular targets remain unknown.…”
Section: Discussionsupporting
confidence: 72%
“…We suppose that the additive and synergistic activities of various phenolics present in CLOs were responsible for distinct tumour‐suppressive effects against rat mammary carcinogenesis in this study. Despite the fact that single phytochemicals demonstrated significant antioxidant and anticancer effects in several studies using different cancer cell lines , we have found that resveratrol administered alone did not indicate any anticancer effects in two repeated studies (with different doses and a way of administration) using the same model of mammary carcinogenesis in rats . It is questionable whether an isolated plant secondary metabolite has the similar anticancer activities as the whole‐plant‐based food containing the cocktail of phytochemicals .…”
Section: Discussionmentioning
confidence: 63%
“…Apigenin has anti-metastatic activity and low cytotoxicity in various cancer cells, but the details of the mechanisms underlying this effect remain unclear [1012]. Our results show that treatment with apigenin at concentrations ranging from 25–50% of the IC50 value inhibits migration and invasion in HCC cell lines.…”
Section: Discussionmentioning
confidence: 67%